A REVIEW ON FOOD-BORNE PATHOGEN LISTERIA MONOCYTOGENES IN FOODS - Shivendra Verma, Abhishek Gupta, Shalini singh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Pesticide residues (PR) found in food is potentially toxic components for humans and can, depending on the means and quantities of individual exposure, cause serious health problems. The most likely exposure is through the direct intake of fresh foods, among the numerous pesticide exposure routes. While the consumption of fresh and minimally processed vegetables is considered safe, there are multiple reports of outbreaks related to these products' contamination. Listeria monocytogenes, a ubiquitous organism that exhibits the capacity to live and replicate at refrigerated temperatures, is among the food-borne pathogens that contaminate vegetables. In recent decades, various pesticide removal methods have studied to eliminate PR from fresh agricultural products and improve consumers' food safety. Many cleaning methods have applied to minimise pesticides, such as surfactants, ozone (O3), ionic solvent, and chlorine treatment. However, none of these strategies has confirmed to effectively eliminate PR without any physical or chemical side effects on the food itself. Therefore a critical need for more efficient, safe and environmentally friendly pest and pesticide removal practices to investigate. Ultrasound-assisted cleaning (UAC) is considered a process of removing pesticides that are environmentally safe and productive and special in eliminating pollutants compared to traditional methods. It is also a time and energy-saving cleaning tool. The most important work on the UAC techniques of organic or inorganic pesticides applied during the growth of fresh vegetables, which are often consumed raw or after limited processing. The review works focuses on Listeria monocytogenes, a multi-pronged approach to managing Listeria monocytogenes in Raw Vegetable and ready-to-eat foods is needed.